Digital wallet and NFC functionality - Andrea Skúladóttir 1992-; Arndís Einarsdóttir 1996-; Helga Lárusdóttir 1996-; Ingibjörg Lilja K. Hafliðadóttir 1993-; Katla Rún Arnórsdóttir 1996- (2021)
Today, digital payment and other services have been growing in the international market. Now people commonly use their phones for paying instead of plastic cards, and digital tickets instead of boarding passes. It is more convenient to have everything in the same place and nowadays people usually have their phone with them, and the physical wallet has slowly started to disappear. Many people have become accustomed to using the phone for such services creating a huge gap in the market for more digital solutions in this field. In Iceland, there are mainly two types of operating systems for phones, Android and iOS. People with iOs phones use Apple Wallet for digital cards and Android users use Google Pay which is not yet available in Iceland. This is partly a research project as well as a software product. There are three parts that make our final software product, our app SmartWallet, the frontend which hosts the distribution page and the backend which controls all the data and connections. SmartWallet is a digital wallet that stores digital passes for its users. SmartWallet is to bridge the gap in the market and provide service for Android users until Google Pay will be available in Iceland. To distribute the passes to customers we need to have a frontend, or a so-called distribution page. The backend supports the functionality which both the app and the distribution page perform. These parts all work together as a whole along with NFC, the research part of this project. NFC stands for Near Field Communication and is a fast-growing field of technology. It is a short-range wireless communication between two devices using electromagnetic radio waves. Apple and Android devices use active NFC and can collect and read information from NFC tags and exchange information. This technology has great potential and can be used to refine and technicalize various processes and objects that we interact with. The project was developed for Smart Solutions. Our contact person at Smart Solutions decided on the main requirements for ...